YTHDC1-mediated microRNA maturation is essential for hematopoietic stem cells maintenance - Hongna Zuo; Jin Liu; Bin Shen; Yue Sheng; Zhenyu Ju; Hu Wang (Cell Death Discovery)
Abstract YTHDC1, a reader of N6-methyladenosine (m6A) modifications on RNA, is posited to exert significant influence over RNA metabolism. Despite its recognized importance, the precise function and underlying mechanisms of YTHDC1 in the preservation of normal hematopoietic stem cell (HSCs) homeostasis remain elusive. Here, we investigated the role of YTHDC1 in normal hematopoiesis and HSCs maintenance in vivo. Utilizing conditional Ythdc1 knockout mice and Ythdc1/Mettl3 double knockout mice, we demonstrated that YTHDC1 is required for HSCs maintenance and self-renewal by regulating microRNA maturation. YTHDC1 deficiency resulted in HSCs apoptosis. Furthermore, we uncovered that YTHDC1 interacts with HP1BP3, a nuclear RNA binding protein involved in microRNA maturation. Deletion of YTHDC1 brought about significant alterations in microRNA levels. However, over-expression of mir-125b, mir-99b, and let-7e partially rescued the functional defect of YTHDC1-null HSCs. Taken together, these findings indicated that the nuclear protein YTHDC1-HP1BP3-microRNA maturation axis is essential for the long-term maintenance of HSCs.